Human immunodeficiency virus and type 2 diabetes. Issue 3 (4th May 2017) - Avari, P.; Devendra, S.
Abstract: The prevalence of diabetes is higher amongst individuals infected with HIV. The major contributor to hyperglycaemia is thought to be iatrogenic, with protease inhibitors being most commonly associated to insulin resistance. This article is to update general practitioners on the diagnosis and management of diabetes in HIV-infected patients. Specific considerations are highlighted including interactions of particular diabetic drugs with antiretroviral therapy (ART). We articulate why the use of Hemoglobin A1c (HbA1c) testing is not recommended as a diagnostic tool.